Characterization of Indonesia citizenship in legal perspective - Winarno Winarno; Muchtarom Muchtarom; Erna Yuliandari (Universitas Negeri Yogyakarta, 2021)
The concept of citizenship covers 3 (three) statuses: legal status, political agent, and identity. Citizenship as legal status is taken into consideration along with the emergence of concept of legal state. The concept is the form of relationship between state and citizens who act in accordance with law possess rights and obligations, and have the right to claim the law's protection. Legal citizenship status for Indonesian citizens can be identified from regulating legal formulation. The present research seeks to find out characterization or attributes of Indonesian citizenship as legal status. Content analysis of legal documents as legal norm regulating Citizenship of the Republic of Indonesia was applied. The legal documents included the 1945 Constitution and Law as regulation of the implementation concerning Citizenship of the Republic of Indonesia. The research results indicate that according to the legal perspective, Indonesian citizenship contains attributes of identity, acceptance of basic social values, and formal content of citizenship. The research concludes that no formulation of material content in the forms of citizens' rights, obligations, and participation was found.